Population dynamics of Citrus tristeza virus (CTV) in single aphid-transmitted sub-isolates of the South African GFMS12 isolate - Biswas, K. K.; Keremane, M. L.; Marais, L. J.; Ramadugu, C.; Lee, R. F. (Frontiers in Plant Science, 2022)
Grapefruit trees in South Africa have been cross protected against severe stem pitting genotypes of Citrus tristeza virus (CTV) since the 1920s using a mild strain initially called Nartia but later referred to as grapefruit mild strain 12 (GFMS12). In the current study, the GFMS12 isolate was used as the source for single aphid transmissions (SAT) using Toxoptera citricida, commonly called the brown citrus aphid (BrCA). The BrCA transmitted CTV sub-isolates were analyzed by the heteroduplex mobility assay (HMA), serological assays, genetic marker analysis (GMA), and selected sub-isolates were biologically indexed. RT PCR of genomic regions was conducted using universal primers followed by cloning the PCR products, HMA and sequence analysis; nine genotypes of CTV were identified in the complex of GFMS12, including both severe and mild genotypes. A single BrCA transmitted up to six CTV genotypes simultaneously in one sub-isolate. The HMA was found to be a rapid, reliable tool for the identification of genotypes and can be useful in the development of CTV management strategies and budwood certification programs.